Analisis Spasial Gambaran Pelaksanaan Program MBG pada Anak Sekolah di Kecamatan Sukadana - Kurniati, Ririn; Selviana, Selviana; Suwarni, Linda (Prominentia Medical Journal, 2026)
Background: In North Kayong district, the prevalence of stunting reached 11.7%, wasting 10.2%, and underweight 10.2%, reflecting significant nutritional risks. The nutrition problem in Sukadana sub-district is a serious challenge that requires comprehensive intervention as it has a significant impact on the growth and quality of life of school-age children. The Free Nutritious Food Program (MBG) comes as a strategy to overcome these problems, but until now there has been no description of the implementation of the MBG program, including in Sukadana sub-district. Objective: To analyze the spatial distribution of MBG program implementation and describe the characteristics, nutritional literacy, and nutritional status of school children receiving the program in Sukadana Sub-district, North Kayong Regency. Methods: Descriptive research with spatial analysis using Geographic Information System (GIS) on 354 primary school students selected through purposive sampling. Data were collected through structured questionnaires, observation, and indepth interviews. Analysis was done descriptively and spatially using QGIS. Results: In Sukadana subdistrict, the spatial distribution of recipients of the nutritious food program (MBG) showed a relatively even distribution with 27.3% of MBG recipient schools within the optimal radius of catering services (≤6 km). The nutrition literacy level showed that 92.7% of respondents had a good understanding of the concept of nutritious food. Nutritional status assessment showed that the majority were in the excellent category with a very low prevalence of nutritional problems (e.g., underweight or overweight) of only 0.3%. Conclusion: The results showed that the MBG program was successful in reaching schools optimally while improving the nutritional literacy of school children. A sustainable program strengthening strategy is needed by considering geographical aspects and improving nutrition education.